Determinan Kejadian Infeksi Saluran Pernafasan Akut (ISPA) di Wilayah Kerja Puskesmas Sukajadi Kota Prabumulih - Putri, Ririn Noviyanti; Nofarika, Dina; Ernia, Rima; Saputra, Rian; Purwanto, Medy (JURNAL KESEHATAN TERAPAN, 2024)
In countries that are still experiencing development, such as Indonesia, ISPA is one of the main causes of death in children. Extrinsic and intrinsic risk factors are related to the occurrence of ARI. The aim of this research is to look at the factors that can influence the incidence of ISPA in toddlers in the Sukajadi Prabumulih Community Health Center Working Area. The research design uses a cross-sectional study with observational analysis. The total sample was 79 mothers who had toddlers aged 24-59 months seeking treatment at the Sukajadi Health Center, Prabumulih City, while the data collection method was purposive sampling. Research findings show that there is a relationship between the incidence of ISPA in toddlers in the Sukajadi Community Health Center Working Area, Prabumulih City and maternal education, employment, income and maternal knowledge. The end of the research is to provide evidence for a conclusion that will enable the community health center to improve its current level of service and take a more proactive approach in providing counseling and educating about ARI in toddlers.